First structural characterization of Pa(iv) in aqueous solution and quantum chemical investigations of the tetravalent actinides up to Bk(iv): the evidence of a curium break. Issue 2 (14th October 2015) - Banik, Nidhu lal; Vallet, Valérie; Réal, Florent; Belmecheri, Réda Mohamed; Schimmelpfennig, Bernd; Rothe, Jörg; Marsac, Rémi; Lindqvist-Reis, Patric; Walther, Clemens; Denecke, Melissa A.; Marquardt, Christian M.
Abstract : The Pa 4+ aqua ion is nine-coordinated like the other early tetravalent actinides whereas a change to eight-coordination occurs at curium. Abstract : More than a century after its discovery the structure of the Pa 4+ ion in acidic aqueous solution has been investigated for the first time experimentally and by quantum chemistry. The combined results of EXAFS data and quantum chemically optimized structures suggest that the Pa 4+ aqua ion has an average of nine water molecules in its first hydration sphere at a mean Pa–O distance of 2.43 Å. The data available for the early tetravalent actinide (An) elements from Th 4+ to Bk 4+ show that the An–O bonds have a pronounced electrostatic character, with bond distances following the same monotonic decreasing trend as the An 4+ ionic radii, with a decrease of the hydration number from nine to eight for the heaviest ions Cm 4+ and Bk 4+ . Being the first open-shell tetravalent actinide, Pa 4+ features a coordination chemistry very similar to its successors. The electronic configuration of all open-shell systems corresponds to occupation of the valence 5f orbitals, without contribution from the 6d orbitals. Our results thus demonstrate that Pa(iv ) resembles its early actinide neighbors.